Structure of myotoxin II, a catalytically inactive Lys49 phospholipase A2 homologue from Atropoides nummifer venom - Murakami, Mário T. [UNESP]; Melo, Cristiane C. [UNESP]; Angulo, Yamileth; Lomonte, Bruno; Arni, Raghuvir K. [UNESP] (International Union of Crystallography (IUCr), 2006)
Lys49 snake-venom phospholipase A2 (PLA2) homologues are highly myotoxic proteins which, although lacking catalytic activity, possess the ability to disrupt biological membranes, inducing significant muscle-tissue loss and permanent disability in severely envenomed patients. Since the structural basis for their toxic activity is still only partially understood, the structure of myotoxin II, a monomeric Lys49 PLA2 homologue from Atropoides nummifer, has been determined at 2.08 Å resolution and the anion-binding site has been characterized. © 2006 International Union of Crystallography. All rights reserved.
Keywords: Atropoides nummifer; myotoxin II, Atropoides nummifer; phospholipase A; snake venom; amino acid sequence; binding site; chemistry; crystallization; molecular genetics; sequence alignment; X ray crystallography; Amino Acid Sequence; Binding Sites; Crotalid Venoms; Crystallization; Crystallography, X-Ray; Molecular Sequence Data; Phospholipases A; Sequence Alignment